Application of a new dynamic 3-D model to investigate human impacts on the fate of mercury in the global ocean. (February 2020) - Kawai, Toru; Sakurai, Takeo; Suzuki, Noriyuki
Abstract: We developed a new global model to predict biogeochemical cycling of mercury in the ocean. We describe and evaluate the model, and discuss mercury levels, distribution, and budgets based on a simulation with a total time span of 260 years. The model is based on a fully coupled atmosphere-ocean chemical transport model, and considers methylated mercury production in the water column, followed by biotransfer to lower-order marine organisms including spatial and temporal variations in partitioning properties. Model validation shows that we can simulate total dissolved mercury (Hg T ) concentrations in the surface ocean with model data differences at a maximum of one order of magnitude. The simulated oceanic Hg T content is currently (2010) 1.6–16.9 times larger than previously modeled estimates. The estimated overall turnover time of oceanic Hg T determined by our model is 320 years, which is shorter than suggested by previous modeling studies. Highlights: Methylated Hg production and decomposition in the water column are modeled. Special/temporal variations of seawater-particle partitioning are considered. Simulations are performed including changes in anthropogenic emissions. Larger Hg contents and shorter Hg turnover time in the ocean are simulated.